1968
DOI: 10.1063/1.1691835
|View full text |Cite
|
Sign up to set email alerts
|

Geodesic Acoustic Waves in Hydromagnetic Systems

Abstract: In toroidal systems with geodesic curvature an electrostatic acoustic mode occurs with plasma motion in the magnetic surfaces, perpendicular to the field. In typical stellarators this mode should dominate ordinary sound waves associated with motion along the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
725
3
10

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 657 publications
(772 citation statements)
references
References 4 publications
34
725
3
10
Order By: Relevance
“…[21] Two new features in the present work are that (1) we retain the effect of ion compressibility, thereby enabling the description of sound waves and drift Kelvin-Helmholtz instabilities [26] and (2) we account for the role of magnetic curvature, thereby enabling our model to describe geodesic acoustic modes (GAM). [27,28] The present paper is organized as follows. Sec.…”
Section: Introductionmentioning
confidence: 99%
“…[21] Two new features in the present work are that (1) we retain the effect of ion compressibility, thereby enabling the description of sound waves and drift Kelvin-Helmholtz instabilities [26] and (2) we account for the role of magnetic curvature, thereby enabling our model to describe geodesic acoustic modes (GAM). [27,28] The present paper is organized as follows. Sec.…”
Section: Introductionmentioning
confidence: 99%
“…They ascribed these modulations to the geodesic acoustic mode (GAM) [21] excited in the tokamak plasma. We started to analyze in detail the large potential oscillations in the tokamak plasma since our measurement of local potential gives directly zonal flows and streamers through −∇Φ × B/B 2 .…”
Section: Short Historymentioning
confidence: 99%
“…The relative radial distance of two HIBPs is varied, and it was found that (1) the radial wavelength of the zonal flows is one or two cm, and that (2) the correlation length of the zonal flows is longer than a few cm. (A peak in the power spectrum around 20 kHz is an oscillating zonal flow, which has been named geodesic acoustic modes (GAMs) [17]. )…”
Section: Zonal Flows and Microscopic Fluctuations In Toroidal Plasmasmentioning
confidence: 99%